2011
DOI: 10.1016/j.ijid.2011.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for community-acquired pneumonia with influenza A/H1N1 in southern Israel

Abstract: In our region CAP with influenza A/H1N1 occurred in younger females of Bedouin Arab origin with less co-morbidity. No difference in mortality was found. We believe that inequalities in socioeconomic conditions could explain our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…However, obesity, pregnancy, and comorbid conditions such as chronic obstructive pulmonary disease (COPD) were shown to increase the severity of the disease in pandemic (H 1 N 1 ) influenza-A pneumonia (3,4). In the current study, the average age of the cases was 47.5±18.6 years and 52.1% had co-morbid diseases.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…However, obesity, pregnancy, and comorbid conditions such as chronic obstructive pulmonary disease (COPD) were shown to increase the severity of the disease in pandemic (H 1 N 1 ) influenza-A pneumonia (3,4). In the current study, the average age of the cases was 47.5±18.6 years and 52.1% had co-morbid diseases.…”
Section: Discussionmentioning
confidence: 59%
“…Unlike seasonal influenza, seen in previous years, thrombocytopenia have been experienced in pandemic (H 1 N 1 ) influenza-A in some studies from Turkey and internationally (3,12,(16)(17)(18)(19). Leukopenia and lymphopenia, which is an indicator of viral infection, is a common finding in pandemic (H 1 N 1 ) influenza-A pneumonia (3,15). Cunha et al (20) have shown that lymphopenia, and thrombocytopenia may play a key role in the diagnosis of pandemic (H 1 N 1 ) influenza-A pneumonia in hospitalized cases.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations